Buddhist–Muslim dialogue: a manual for Buddhist–Muslim understanding - Mohamed Ashath, Mohamed Shafeen; Madusanka, Ramesh (Tanweer Institute, 2025)
Together, Dr Mohamed Ashath and Ramesh Madusanka, we stand at the threshold of a remarkable journey encapsulated within the pages of " Buddhist–Muslim Dialogue: A Manual for Buddhist–Muslim Understanding." In this collaborative effort, we merge our voices and insights, driven by a shared vision of promoting understanding and harmony between two respected spiritual traditions.